Nuevos registros de arañas (Arachnida: Araneae) para México y listado actualizado de la araneofauna del estado de Coahuila - Desales-Lara, Marco Antonio; Jiménez, María Luisa; Corcuera, Pablo (Instituto de Ecología, A.C., 2018)
Four new records of spiders for Mexico (Herpyllus schwarzi, Nodocion rufithoracicus Phrurotimpus woodburyi and Thanatus altimontis) and four for the state of Coahuila (Euagrus chisoseus, Herpyllus propinquus, Latrodectus hesperus and Titanebo mexicanus) are presented. An updated list of 178 spider species of Coahuila in 100 genera and 32 families is given. The families with highest number of species were Gnaphosidae (39), Lycosidae (22) and Salticidae (15). The state of Coahuila ranks twelfth in the diversity of spiders in Mexico.